Acutihumerus patagoniensis (Sieg, 1986) (Tanaidacea: Kalliapseudidae): supplementary description and remarks on its taxonomic status - Giachetti, Clara Belen; Roccatagliata, Daniel (Zootaxa, 2014)
Acutihumerus patagoniensis (Sieg, 1986) was originally described based on a single specimen from Golfo Nuevo, northern Patagonia, Argentina. Over 3000 specimens referable to this species from just a few miles of its type locality are now available. Based on these specimens, the description of A. patagoniensis is completed and the ontogenetic changes of the male cheliped are described and illustrated. Acutihumerus patagoniensis has recently been considered a junior synonym of A. cavooreni (Băcescu & Absalao, 1985) from southern Brazil. However, these species can be distinguished mainly by the male chela: A. patagoniensis has a much wider notch palm than A. cavooreni. Furthermore, most of the males herein reported from off the Río de la Plata have a chela with a narrow notch, a fact that suggests that this area might be a zone of hybridization or contact between A. patagoniensis and A. cavooreni. Hence, we claim that the recently proposed synonymy has not been proven, and the resolution of this taxonomic problem must await additional specimens of A. cavooreni from its type locality (Rio Grande do Sul, Brazil).